Arrhythmic death and ICD implantation after myocardial infarction - Federico Lombardi (Heart International, 2006)
Arrhythmic death remains one of the most important causes of mortality after an acute myocardial infarction also in the revascularization era. As a consequence, identification of patients at risk should be performed before discharge. Unfortunately, in the clinical practice, this evaluation is mainly based on detection of a depressed left ventricular ejection. This approach, however, cannot adequately distinguish arrhythmic versus non-arrhythmic risk. This issue is of critical relevance when considering that arrhythmic death can be significantly reduced by appropriate interventions of implantable cardioverter defibrillator. Available evidence, however, indicates that in the first month after myocardial infarction, device implantation does not significantly reduce cardiac mortality: it seems that the reduction of arrhythmic death is counterbalanced by an increase in rate of death from non arrhythmic cause. It is therefore to be hoped that, in the future, arrhythmic risk evaluation will be based not only on the extent of left ventricular dysfunction but also on the analysis of other risk markers such as those reflecting autonomic dysfunction, cardiac electrical instability and presence of subclinical inflammation.